Risk Factors in Predicting Prognosis of Neonatal Bacterial Meningitis—A Systematic Review - Mao, Dan-Hua; Miao, Jing-Kun; Zou, Xian; Chen, Na; Yu, Lin-Chao; Lai, Xin; Qiao, Meng-Yuan; Chen, Qi-Xiong (Frontiers in Neurology, 2018)
Background: Neonatal bacterial meningitis is a severe infection with high mortality and morbidity. It is necessary to identify factors associated with a high risk of a poor prognosis so that we can prevent them with more appropriate treatments. This study was performed to summarize the prognostic factors known to predict adverse outcomes in neonatal bacterial meningitis. Methods: The Medline/PubMed, Cochrane Library and Embase databases were searched for studies of prognostic risk factors in neonates with bacterial meningitis. Studies published from the initiation of the database to April 30th, 2017 were included. The quality of cohort studies was assessed by the Newcastle-Ottawa Scale (NOS). The quality of cross-section studies was assessed by the Agency for Healthcare Research and Quality (AHRQ) scale. Each prognostic factor known to cause adverse outcomes is summarized. Results: Sixteen studies were identified, including 7 cohort studies and 9 cross section studies. Seizure and high protein levels in the cerebrospinal fluid (CSF) predict a poor prognosis in this disease. Coma, the need for ventilation support, and leukopenia also had some value for predicting poor prognoses. A bulging anterior fontanelle was valuable for predicting mortality. Low CSF glucose levels, thrombocytopenia, gestational age (GA) <37 weeks and an altered sensorium were correlated with a poor prognosis. A birth weight <2500 g, early onset meningitis and positive CSF cultures were correlated with mortality. Conclusions: This study provides a preliminary exploration of prognostic factors in neonatal bacterial meningitis and thereby fills some of the gaps in the study of prognoses in this disease. These prognostic factors can be used to predict and estimate outcomes in neonatal bacterial meningitis. Without a meta-analysis, the reliability of these factors cannot be assured. In addition, these results emphasize that there is an urgent need for a standardized protocol for follow-up and well-designed prognostic studies in neonatal bacterial meningitis.